Geneza i doktryna dualizmu słowiańskiego w średniowieczu = THE ORIGIN AND DOCTRINE OF SLAVIC DUALISMIN THE MIDDLE AGES - Czarnecki, Piotr (Studia religiologica, 2008)
The article touches upon the poorly source-documented issue of Slavic dualism, a heresy which existed in the 12th-to-15th centuries in Dalmatia and Bosnia. The dearth of vernacular sources makes it difficult to trace either the history or the doctrine of Slavic dualists. On the other hand, Inquisition sources concerning Italian Cathari mention an „ordo Sclavoniae,” next to „ordo Bulgarie” and „ordo Drugonthiae,” as one of three main dualist currents to inspire Western heretics. The article tries to determine the identity of the Slavic version of the dualist heresy by inquiring into its origin and doctrinal peculiarities which distinguished it from its contemporary variants of dualism. In order to cast a fuller light on the subject, it is worth bringing together what laconic Slavic or Byzantine sources are available and the Inquisition’s comprehensive documentation covering especially Italy, including its Cathari, who were described as Slavs.